(untitled) (The Research of Medical Science Review, 2025)
Background: Breast cancer is the most frequently diagnosed female cancer globally, with Pakistan holding the highest incidence rate in Asia. Despite the critical importance of early diagnosis and treatment, Pakistani women often seek medical help at advanced stages due to various socio-economic and cultural barriers. Objectives: This study aims to explore the individual, socio-cultural, and structural barriers that hinder timely breast cancer diagnosis and treatment in Punjab, Pakistan. Methodology: Employing a qualitative methodology, the research involved in- depth interviews with 45 breast cancer patients. The study focused on identifying key obstacles such as lack of awareness, reliance on spiritual healing, feminine sensitivity, stigmatization, aversion to male doctors, economic limitations, and inadequate medical services. Results: The findings highlight significant barriers to early diagnosis and treatment, including socio-cultural factors like stigmatization and feminine sensitivity, individual factors such as lack of awareness and reliance on spiritual healing, and structural barriers like economic limitations and inadequate medical services. These barriers contribute to delayed medical intervention and increased mortality and morbidity rates.